Biofuel production from fruit and vegetable market waste and mature landfill leachate by an active filter-anaerobic digestion integrated system - F. Fazzino (Elsevier, 2021)
The management of municipal solid wastes represents one of the biggest challenges for the actual implementation of the circular economy. While the main “dry” fractions (such as plastics and paper) can be easily recycled, treatments for both the valorisation of the organic waste and for the disposal of leachate (produced by the landfilling of unsorted municipal waste) often turn out to be inadequate and expensive. Particularly, the leachate management is a critical issue since the mature landfill leachate (MLL) must be treated for decades even after the landfill closure. In this study, an innovative approach is proposed and it consists in an integrated system of active filters and anaerobic reactors for the simultaneous treatment of both waste streams (i.e., organic waste and MLL). Firstly, bio-refractory compounds (e.g., metals) present in MLL are removed by filtration on active materials (i.e., zero valent iron (ZVI) and granular activated carbon (GAC) or ZVI and Lapillus mixtures). The so-treated MLLs are then used as nutrient solutions for the anaerobic digestion (AD) of market wastes (MW) to optimize the C/N ratio. Moreover, during the anaerobic digestion, granular active carbon (GAC) is added in some reactors along with the feeding solution (substrate and pre-treated MLLs) to retain possible refractory or toxic compounds and to facilitate microorganisms’ activities by promoting the direct interspecies electron transfer mechanism. MLLs, used as nutrient solutions, lead to a stable AD of MW with a methane yield of about 0.260 NL/gVSadded. GAC is proved to be also efficient in the enhancement of the methane production as higher methane yields (about 0.302 NL/gVSadded) are obtained in reactors where it is added as a supplement.